Marketing strategy of sports companies using the Olympic Games - Kim, D. K.; Han, J. W. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The Olympic Games have been widely accepted as a perfect opportunity to global companies to enhance their image of brands and products. Above all, the competition among sports equipment companies appears more severe. During the Olympic Games, the sports equipment companies utilize a marketing strategy through sports by advertising which players wear their brand uniform, or what kind of cutting-edge technology is used for their equipment. Such a marketing strategy enables consumers to differentiate a brand with the others and provide them with trust in the brand. To this end, the purpose of this study was to examine how sports companies use a marketing strategy through sport during the Olympic Games. The study will focus on sport shoes and sports apparel by reviewing existing literature. Methods Since the nature of this study was to examine how marketing strategies of sports companies were used during the Olympic Games, literature was reviewed which mentioned real marketing practices from the sport companies participating in the current Olympic Games including 1996 Atlanta, 2000 Sydney, and 2004 Athens. Results Firstly, the marketing strategies of companies participating in the Olympic Games as an official sponsor and partner can be categorized as follows. (1) Companies take part in the Olympic Games in order to reinforce their status as a global company. Some companies who have already secured the highest share in the market participate in the Olympic Games in order to deter rival companies and maintain a favourable image. (2) Companies try to advertise their brand image as a pioneer. Some companies utilize the Games in an attempt to enhance their image as a high technology company. (3) Companies try to advance from a local brand to a global brand. Local companies try to target a global market using the Olympic Games. (4) Companies utilize an endorsement marketing strategy for celebrities. For example, sport companies use this strategy by sponsoring celebrities` shoes or uniforms. (5) Companies exploit an ambush marketing strategy. Some companies unable to participate in the Olympic Games as an official sponsor or partner can have similar benefits to them, as if they act official sponsors or partners. Secondly, sports equipment companies not only sponsor players inside venues and but also promote media conferences with famous players and directly host various types of events outside venues to attract attention from media. Thirdly, sports equipment companies invest heavily in producing equipments with cutting-edge technology in order for players to reduce time and to have best conditions for competition. For example, a company introduced a streamline shape uniform to a track athlete, who won the women`s 400m competition in 2000 Sydney Olympic Games. As a result, the company was able to make a good impression on consumers about its high technology with sport equipment. Another company devised the upgrade version of the full body suit, called the "jet concept full body", for the swimmer in the2004 Athens Olympic Games. The player who wore this suit attributed his win to the high technology swim suit. Discussion / Conclusions Developing new equipment has enabled companies to advertise their equipment globally during the Olympic Games, which is acknowledged as a more effective marketing strategy than any other marketing tools. Therefore, sports companies should actively find a way to participate in the Olympic Games as an official or unofficial sponsor. In future research, it is recommended to empirically test the effectiveness of sponsoring the Olympic Games comparing pre- and post-Olympics.